Identification and Functional Characterization of Genes Involved in the Biosynthesis of Caffeoylquinic Acids in Sunflower (Helianthus annuus L.) - Cheevarungnapakul, Ketthida; Khaksar, Gholamreza; Panpetch, Pawinee; Boonjing, Patwira; Sirikantaramas, Supaart (Frontiers in Plant Science, 2019)
Sunflower (Helianthus annuus L.) sprouts accumulate high amounts of caffeoylquinic acids (CQAs) including chlorogenic acid (5-CQA) and 1,5-diCQA. These compounds, which can be found in many plants, including tomato, globe artichoke, and chicory, have many health benefits, including antioxidant, antihepatotoxic, and antiglycative activities. However, CQA profiles and biosynthesis have not previously been studied in sunflower sprouts. In the present study, we found that 5-CQA and 1,5-diCQA were the major CQAs found in sunflower sprouts. We also identified minor accumulation of other CQAs, namely 3-CQA, 4-CQA, 3,4-diCQA, and 4,5-diCQA. According to genome-wide identification and phylogenetic analysis of genes involved in CQA biosynthesis in sunflower, three genes (HaHQT1, HaHQT2, and HaHQT3) encoding hydroxycinnamoyl CoA:quinate hydroxycinnamoyl transferase (HQT), and two genes (HaHCT1 and HaHCT2) encoding hydroxycinnamoyl CoA:shikimate/quinate hydroxycinnamoyl transferase (HCT) were identified. Expression analysis of these five genes in hypocotyls and cotyledons strongly suggested that HaHQT2 could be the main enzyme responsible for CQA biosynthesis, as HaHQT2 had the highest expression levels. In addition, when transiently expressed in the leaves of Nicotiana benthamiana, all three HaHQTs, which were soluble and not membrane-bound enzymes, could increase the content of 5-CQA by up to 94% compared to that in a control. Overall, our results increase understanding of CQA biosynthesis in sunflower sprouts and could be exploited by plant breeders to enhance accumulation of health-promoting CQAs in these plants.